REVITALISASI NILAI ISLAM MELAYU DI ERA DIGITAL: INTEGRASI PEMIKIRAN TOKOH KLASIK DAN MODERN DALAM PEMBENTUKAN KARAKTER SISWA SMA NEGERI 1 LAWANG KIDUL: PENDAHULUAN, METODOLOGI, HASIL dan DISKUSI, KESIMPULAN - Uswatun Hasanah; Siska Wulandari; Muhamad Fauzi; Abu Mansu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the revitalization of Malay Islamic values in shaping students’ character in the digital era through the integration of classical and modern Islamic thought. Using a descriptive qualitative approach, the research was conducted at SMA Negeri 1 Lawang Kidul through interviews, observations, and documentation involving Islamic Education teachers and students. The findings reveal that Malay Islamic values such as politeness, respect for teachers, and responsibility are still understood by students but have not been fully internalized in their digital behavior. The integration of classical scholars such as Hamzah Fansuri, Nuruddin al-Raniri, and Raja Ali Haji with modern thinkers such as Syed Muhammad Naquib al-Attas, Wan Mohd Nor Wan Daud, and Osman Bakar produced a revitalization model based on three main pillars: Digital Adab, Malay Islamic Character Education, and Cultural and Spiritual Literacy. This model effectively fosters digital ethics, discipline, and pride in Islamic-Malay identity. Thus, the revitalization of Malay Islamic values serves as a strategic innovation in character education that is contextual, holistic, and relevant to the challenges of the digital globalization era.